2019
DOI: 10.3989/mc.2019.05818
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soda-lime waste glass microparticles on workability and thermal properties of portland cement compounds

Abstract: Numerous studies have investigated the use of waste glass as a partial substitution in Portland cement. Nonetheless, it seems there is no consensus about the influence of particle size and color on the behavior of the compounds. This work investigates the influence of soda-lime glass microparticles on the properties of cement and mortar in both fresh and hardened states. The effects of partial substitution (10 and 20%) of the cement by colorless and amber glass particles with dimensions of approximately 9.5 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The results of the application of glass powders in different percentages (lower than 20%) indicated a slight increase in the compressive strength (Lee et al, 2011) and the tensile strength of the concrete. Research (Sales et al, 2017;Alvarenga et al, 2019) on the incorporation of glass waste as a fine aggregate in mortar or as a substitute for cement concluded that the presence of glass tends to reduce the heat conduction in these composites, improving thermal insulation properties.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the application of glass powders in different percentages (lower than 20%) indicated a slight increase in the compressive strength (Lee et al, 2011) and the tensile strength of the concrete. Research (Sales et al, 2017;Alvarenga et al, 2019) on the incorporation of glass waste as a fine aggregate in mortar or as a substitute for cement concluded that the presence of glass tends to reduce the heat conduction in these composites, improving thermal insulation properties.…”
Section: Introductionmentioning
confidence: 99%